2020
DOI: 10.1038/s41467-020-18786-x
|View full text |Cite
|
Sign up to set email alerts
|

Early prediction of disease progression in COVID-19 pneumonia patients with chest CT and clinical characteristics

Abstract: The outbreak of coronavirus disease 2019 (COVID-19) has rapidly spread to become a worldwide emergency. Early identification of patients at risk of progression may facilitate more individually aligned treatment plans and optimized utilization of medical resource. Here we conducted a multicenter retrospective study involving patients with moderate COVID-19 pneumonia to investigate the utility of chest computed tomography (CT) and clinical characteristics to risk-stratify the patients. Our results show that CT s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
183
4
16

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(226 citation statements)
references
References 39 publications
16
183
4
16
Order By: Relevance
“…First, this is a monocentric work, suggesting that our findings should be validated by multi-institutional trials. However, our results are overall in line with previous works performed both in Western [ 12 ] and in Eastern [ 10 , 11 ] scenarios of the pandemic, suggesting they are reasonably generalizable. Second, we limited our models to imaging findings, excluding patients’ comorbidities and other clinical factors.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…First, this is a monocentric work, suggesting that our findings should be validated by multi-institutional trials. However, our results are overall in line with previous works performed both in Western [ 12 ] and in Eastern [ 10 , 11 ] scenarios of the pandemic, suggesting they are reasonably generalizable. Second, we limited our models to imaging findings, excluding patients’ comorbidities and other clinical factors.…”
Section: Discussionsupporting
confidence: 92%
“…When considering experienced readers only, severe disease was independently predicted also by OP pattern (in the case of R1), and consolidation > 2 (in the case of R2), in accordance with higher pairwise agreement on those two features ( k = 0.59 and 0.64, respectively). Our findings are in line with previous studies showing substantial-to-almost perfect inter-reader agreement for most CT features [ 14 , 16 ], and the capability of semi-quantitative or quantitative evaluation of lung involvement [ 10 , 12 ] to predict disease worsening. Overall, our results provide reliable potential markers for disease progression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Analysis of the demographics of our studied sample showed that patients who received HCQ were significantly of older age, which could be associated with a more severe HCQ-requiring presentation. Although this is an extrapolation from our data, age has reportedly been associated with a more severe progression of the disease [ 25 28 ]. However, a recent study quantifying the isolated effect of age on severity of COVID-19 outcomes concluded a minimal influence of age after adjusting for important age-dependent risk factors (e.g., diabetes, hypertension, cardiovascular disease (CVD) etc.)…”
Section: Discussionsupporting
confidence: 49%
“…Non-severe cases display symptoms such as fever, dry cough, and fatigue, but have a good prognosis. By contrast, up to 10-15% of hospitalized patients progress to a severe form of the disease and may develop pneumonia, acute respiratory distress syndrome, and multiple organ failure, requiring long stays in intensive care units (ICU) [1][2][3].…”
Section: Introductionmentioning
confidence: 99%